(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses issues related to the concept of "freedom", their consideration from the point of view of ancient philosophy. The questions of the influence and continuity of ancient philosophical thought on the philosophical views of L.N. Tolstoy.